IMPLEMENTATION OF FORWARD AND INVERSE KINEMATICS ALGORYTHM IN 18 DEGREES OF FREEDOM SIX LEGGED ROBOT (HEXAPOD) MOVEMENT CONTROL - RACHMATULLAH (NIM : 13206071) ; pembimbing : Dr. Ir. Hilwadi Hindersah ; Dr. Ir. Kusprasa, SYAWALUDIN
In this final project, a legged robot that resembles many-legged animals such as ant (ant: six-legged) will be made. Robot is designed to have six legs, each leg will have three joints. In other words, the robot will have a total of 18 degrees of freedom. The movement of the robot will be designed and analyzed using the theory of forward and inverse kinematics. The forward kinematics analysis aims to find the value of the position the end of legs as a result of a combination of hinge leg angles, while inverse kinematics analysis aims to find the combination of the hinge leg angles required to achieve a certain final position of the end of a robot leg. By using analysis and implementation of this algorithm, robot is expected to be able to move smoothly and seamlessly in performing static movement (feet remain in ground while robotÃ‚Â’s body moving), dynamic movement (robot moves by walking), or a combination of both. Furthermore, at the end of the project the effect of applying this algorithm on the fineness robot movement, the speed of the robot moving step, and the slip factor that occurs between the ends of the legs of the robot with the terrain in its path when it stepped, will be tested and observed. Utilization of this robot is more directed especially to the entertainment or the research development of legged robot motion control in general. It also answered the challenge of creating legged robots that can move quickly and complete missions on Indonesian Smart Robot Contest (KRCI) - Fire Fighting Robot - Legged Robot iii Division, which are regularly held each year and followed by many universities in Indonesia.